2022
DOI: 10.1371/journal.pone.0264389
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of face masks in blocking the transmission of SARS-CoV-2: A preliminary evaluation of masks used by SARS-CoV-2-infected individuals

Abstract: In 2019, a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is transmitted via the airborne route, caused a new pandemic namely, “coronavirus disease 2019” (COVID-19). Although the effectiveness of face masks to prevent the transmission of SARS-CoV-2 is debated, no study has evaluated the virus-blocking efficacy of masks used by patients. We aimed to evaluate this efficacy of masks used by SARS-CoV-2-infected individuals. Data, masks used, and nasopharyngeal swab samples were obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…The results confirm that both MNC and FFP2 masks are an effective protection against aerosol particle and large particle emission during ENT procedures [30][31][32]. Both mask types reduced the particle emission down to the background noise level of the OR.…”
Section: Discussionsupporting
confidence: 72%
“…The results confirm that both MNC and FFP2 masks are an effective protection against aerosol particle and large particle emission during ENT procedures [30][31][32]. Both mask types reduced the particle emission down to the background noise level of the OR.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, there is, as far as we are aware, no information available on what happens to the viral load in masks after use. A recent study has shown that, typically, a face mask contains about 2500 virus particles after 2–3 h use by an infected patient [ 52 ]. There is clearly a potential for virus particles to survive and be released back into the environment, but with the treatment described, up to 98% of these particles will have been rendered non-infectious.…”
Section: Discussionmentioning
confidence: 99%
“…Physical barriers are required and are therefore very useful to protect ourselves and the others from infection, contagion and community spreading of the virus, lowering the concomitant emergence of viral variants (Střížová et al, 2020;Swain, 2020;Mello et al, 2022), which threatens individual and community immunity that might have been generated during previous infections or by vaccines (Arora et al, 2021;Boehm et al, 2021;Caniels et al, 2021;Arora et al, 2022;Salehi-Vaziri et al, 2022), as it has happened with the appearance of several Omicron VOCs (Cao et al, 2022;Flemming, 2022;Hachmann et al, 2022). Therefore, vaccines are the tools to elicit immunity against SARS-CoV-2 infection, reinfection by VOCs and severe COVID-19 disease, where face masks enhance vaccine efficiency in this crucial community and worldwide task.…”
Section: Covid-19 Vaccines By Nano-based Strategies: Prevention and T...mentioning
confidence: 99%